Elucidating the molecular mechanism of TET2 function in hematopoiesis - Huang, W (2021)
DNA modifications are epigenetic marks deposited throughout the mammalian genome and play an important role in gene regulation in normal and malignant biological processes. Biological DNA modifications are introduced by DNA methyltransferases (DNMT) and dioxygenases of ten- eleven translocation (TET) family. DNMT proteins can convert cytosine into 5-methylcytosine. TET proteins catalyze the oxidation of 5mC to 5-hydroxymethylcytosine, 5-formylcytosine and 5-carboxylcytosine. These oxidized forms of cytosine stay in the DNA or result in DNA demethylation. TET2, a member of TET family proteins, is one of the most frequently mutated genes in hematological malignancies. While TET2 has roles in normal hematopoiesis, including stem cell self-renewal and specific lineage commitment, the exact molecular mechanism of its function still remains unknown. The aims of the project are to identify the role of TET2 in regulating hematopoietic gene expression and to identify the molecular partners of TET2 in the hematopoietic-associated context, thus to arrive at the mechanism of action of TET2 in normal hematopoiesis.